2012
DOI: 10.1093/eurheartj/ehs424
|View full text |Cite
|
Sign up to set email alerts
|

A diabetes-predictive amino acid score and future cardiovascular disease

Abstract: This study identifies branched-chain and aromatic amino acids as novel markers of CVD development and as an early link between diabetes and CVD susceptibility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
196
2
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 241 publications
(213 citation statements)
references
References 30 publications
14
196
2
1
Order By: Relevance
“…For each diet, we examined the direction of change in the concentrations of the metabolites that have been shown to predict the risk of type 2 diabetes (31,32,(38)(39)(40)(41)(42). We annotated each metabolite by whether the change by diet was in the direction that increased or decreased risk of disease.…”
Section: Disease Riskmentioning
confidence: 99%
See 1 more Smart Citation
“…For each diet, we examined the direction of change in the concentrations of the metabolites that have been shown to predict the risk of type 2 diabetes (31,32,(38)(39)(40)(41)(42). We annotated each metabolite by whether the change by diet was in the direction that increased or decreased risk of disease.…”
Section: Disease Riskmentioning
confidence: 99%
“…Multiple metabolites that have been linked to risk of type 2 diabetes (31,32,(38)(39)(40)(41)(42) showed strong or moderate associations with diet, including amino acids (isoleucine, leucine, valine, tyrosine, serine and glutamine), lipids (C18:2 lysophosphatidylethanolamine (LPE), C22:6 LPE, C56:9 TAG, C58:10 TAG, and C60:12 TAG), and others (2-aminoadipate, betaine, and C3 carnitine) as depicted in Supplemental Figures 5 and 6. The concordance between the metabolite profile that predicts type 2 diabetes risk and the dietassociated changes varied across classes of metabolites.…”
Section: Effect Of Diet On Metabolites That Predict Disease Riskmentioning
confidence: 99%
“…106 The 3 amino acids most strongly associated with diabetes mellitus (isoleucine, tyrosine, and phenylalanine) were subsequently shown to predict incident atherosclerotic cardiovascular disease (MI or stroke), carotid intima-media thickness and plaques, and exerciseinduced myocardial ischemia. 107 These findings highlight a potential key role of amino acid metabolism in early diabetes mellitus development, and they point to a potential link between type 2 diabetes mellitus and susceptibility to atherosclerotic cardiovascular disease.…”
Section: Musunuru Et Al Expressed Genome In Cardiovascular Diseases Amentioning
confidence: 82%
“…A previous study reported the integration of metabolite levels of bio fluids and other biochemical information (e.g., glucose and HbA1c) could better reflect T2DM risk than a single established risk factor [29,[39][40][41][42][43][44][45][46]. Determination of the levels of several amino acid and other metabolites that showed a marked change after metformin treatment could significantly improve drug response prediction and serve as markers for the diagnosis of T2DM.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies suggested that higher plasma amino acid level profile could reflect hyperglycemia odds and incidence of type 2 diabetes mellitus hazards assessment [29,[43][44][45]. Phenylalanine and tyrosine could be a strong predictor of diabetes [46], further theses AAAs are future biomarkers of long-term impaired insulin sensitivity.…”
Section: Discussionmentioning
confidence: 99%